Nitrogen Fertilizer Timing and Phosphorus and Potassium Fertilization Rates for Established Endophyte-Free Tall Fescue - D. W. Sweeney; J. K. Farney; J. L. Moyer (Kansas Agricultural Experiment Station Research Reports, 2019)
A tall fescue production study was conducted at two locations, beginning in the fall of 2016 and the fall of 2017. At both sites, phosphorus (P) fertilization rate only affected the spring harvest, with few differences in yield. Applying nitrogen (N) in late fall or late winter resulted in greater spring yields than applying N in spring or not applying N. However, at Site 1 in 2017 fall harvest yields were greater from the spring N application, but this response was less at Site 2 in 2018. In both years, applying N increased tall fescue yield, but at Site 2 the yield differences from N timings were greater.
Keywords: nitrogen; phosphorus; potassium; tall fescue